Valdosta State University Faculty Senate Committee on Committees, Minutes, August 8, 2016. - Faculty Senate (Valdosta State University, 2016)
VSU Faculty Senate: Committee on Committees, Minutes, August 8, 2016 UA/19/1/0_ER1-001 B917506E-5997-43B4-86B2-21A6D68C88B8 Valdosta State University Faculty Senate Committee on Committees, Minutes, August 8, 2016.
Keywords: Faculty Senate